The Complexity of Pain Management in Children Affected by Mucopolysaccharidoses - Sabrina Congedi; Chiara Di Pede; Maurizio Scarpa; Angelica Rampazzo; Franca Benini (Hindawi Limited, 2017)
Mucopolysaccharidoses (MPSs) are a group of rare, genetic lysosomal storage disorders. They are caused by deficiencies of the lysosomal enzymes involved in the degradation of glycosaminoglycans (GAGs). Pain is a common feature in mucopolysaccharidoses. However, the pathophysiology of pain in this group of diseases is still unclear and genesis of pain is multifactorial. Currently, poor data about pain management in these patients are available. Here, we present our clinical experience in complex pain management in three children with MPS.